2022
DOI: 10.21468/scipostphys.12.3.094
|View full text |Cite
|
Sign up to set email alerts
|

Multimode-polariton superradiance via Floquet engineering

Abstract: We consider an ensemble of ultracold bosonic atoms within a near-planar cavity, driven by a far detuned laser whose phase is modulated at a frequency comparable to the transverse cavity mode spacing. We show that a strong, dispersive atom-photon coupling can be reached for many transverse cavity modes at once. The resulting Floquet polaritons involve a superposition of a set of cavity modes with a density excitation of the atomic cloud. The mutual interactions between these modes lead to distinct avoided cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It has been shown that population inversion of Floquet states can occur in driven systems [39][40][41]. Floquet theory itself presents a method to describe the effective dressed states in driven systems and their population, and is applicable to driven dissipative cavity systems [42,43], in particular.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that population inversion of Floquet states can occur in driven systems [39][40][41]. Floquet theory itself presents a method to describe the effective dressed states in driven systems and their population, and is applicable to driven dissipative cavity systems [42,43], in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Floquet theory itself presents a method to describe the effective dressed states in driven systems and their population, and is in particular also applicable to driven dissipative cavity systems [36,37]. We present the emergence of a Floquet-assisted superradiant phase (FSP) in the dissipative Dicke model under the influence of circularly polarized driving of the two-level systems, reminiscent of the Rabi model.…”
mentioning
confidence: 99%